The Paleozoic northern margin of the Tarim Craton: Passive or active? - Ge, Rongfeng; Zhu, W.; Wu, H.; Zheng, B.; Zhu, X.; He, J. (Elsevier BV, 2012)
Whether the northern Tarim Craton was an active or passive continental margin during the Paleozoic is vital to our understanding of the subduction polarity of paleo-oceanic plates in the Tianshan Orogen and the accretion history of the southwestern Central Asian Orogenic Belt. We identified undeformed granitoids intruding into the Paleoproterozoic metamorphic rocks in the Korla area at the northern Tarim Craton. Zircon LA-ICP-MS U-Pb dating of three samples from a porphyritic granodiorite pluton yields three indistinguishable crystallization ages: 420.6±2.3Ma (MSWD=1.02, n=27), 421.7±2.8Ma (MSWD=0.75, n=17) and 419.8±3.3Ma (MSWD=1.10, n=13), highlighting a late Early Paleozoic magmatic event. In-situ zircon Hf isotope data of the youngest zircon population (ca. 420Ma) vary in large ranges (up to 11 epsilon Hf units for single sample), with the lowest e Hf (t) value (-14.2) approaching the evolution line of the Early Paleoproterozoic crust in the northern Tarim Craton, suggesting magma mixing between the old crust-derived magma and the relatively juvenile materials probably derived from depleted mantle. Geochemical data suggest that these granitoids are metaluminous, high K calc-alkaline granodiorite. They show a moderately differentiated REE pattern with insignificant Eu anomalies and are relatively depleted in Nb, Ta, Ti, P, but enriched in K and Ba, resembling Andean arc granite. In various discrimination diagrams, all samples consistently plot into the subduction-related areas. These geochemical and isotopic features suggest that this magmatic event probably occurred in an Andean-type continental arc. Therefore, if the northern Tarim Craton was a passive continental margin in the Early Paleozoic, it must have changed into an active margin at least since ca. 420Ma, probably as early as the Ordovician-Silurian boundary, necessitating a southward subduction of the South-Tianshan Ocean. Considering the coeval arc magmatism on the Central Tianshan Block, a divergent double subduction model for the South-Tianshan Ocean is tentatively proposed.